Replacement Beef Cow Valuation under Data Availability Constraints - Hagerman, Amy D.; Thompson, Jada M.; Ham, Charlotte; Johnson, Kamina K. (Frontiers in Veterinary Science, 2017)
Economists are often tasked with estimating the benefits or costs associated with livestock production losses; however, lack of available data or absence of consistent reporting can reduce the accuracy of these valuations. This work looks at three potential estimation techniques for determining the value for replacement beef cows with varying types of market data to proxy constrained data availability and discusses the potential margin of error for each technique. Oklahoma bred replacement cows are valued using hedonic pricing based on Oklahoma bred cow data—a best case scenario--vector error correction modeling (VECM) based on national cow sales data, and cost-of-production (COP) based on just a representative enterprise budget and very limited sales data. Each method was then used to perform a within-sample forecast of 2016 January to December and forecasts are compared to the 2016 monthly observed market prices in Oklahoma using the mean absolute percent error (MAPE). Hedonic pricing methods tend to over-value for within-sample forecasting but performed best, as measured by mean absolute percent error for high quality cows. The VECM tended to undervalue cows, but performed best for younger animals. COP performed well, compared to the more data intensive methods. Examining each method individually across 8 representative replacement beef female types, the VECM forecast resulted in a MAPE under 10% for 33% of forecasted months, followed by hedonic pricing at 24% of the forecasted months and cost of production at 14% of the forecasted months for average quality beef females. For high quality females, the hedonic pricing method worked best producing a MAPE under 10% in 36% of the forecasted months followed by the COP method at 21% of months and the VECM at 14% of the forecasted months. These results suggested that livestock valuation method selection was not one-size-fits-all and may need to vary based not only on the data available, but also on the characteristics (e.g. quality or age) of the livestock being valued.